2018
DOI: 10.1002/jbio.201700267
|View full text |Cite
|
Sign up to set email alerts
|

Imaging molecular signatures for clinical detection of scleroderma in the hand by multispectral photoacoustic elastic tomography

Abstract: Scleroderma (SD) is a rare autoimmune disease, which is divided into 2 categories: the localized SD and systemic SD. The localized SD mainly causes skin thickening of the fingers, whereas the systemic SD can further affect the blood vessels and internal organs. In this pilot study, the multispectral photoacoustic elastic tomography (PAET) imaging technique was used to recover the quantitative physiological and elastic properties of biological tissues for the diagnosis of SD. Three healthy subjects and 3 SD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Our results show reduced values of haemoglobin in subcutaneous finger tissue of patients with SSc compared to healthy volunteers. This observation is consistent with first experimental findings in SSc and generally in accordance with the current concept of microvascular dysfunction and subsequent development of DU . Second, we observed significantly reduced values of haemoglobin in patients with a progressive disease burden compared to SSc patients with a stable disease activity or healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show reduced values of haemoglobin in subcutaneous finger tissue of patients with SSc compared to healthy volunteers. This observation is consistent with first experimental findings in SSc and generally in accordance with the current concept of microvascular dysfunction and subsequent development of DU . Second, we observed significantly reduced values of haemoglobin in patients with a progressive disease burden compared to SSc patients with a stable disease activity or healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its application in preclinical models of disease , MSOT has recently proven to be a promising tool in first clinical applications . Recent studies have shown the general capability of MSOT for dedicated vascular imaging .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Label-free PA imaging has already been employed clinically for the detection of breast cancer, 5 thyroid cancer, 6 inflammatory arthritis, 7 and scleroderma. 8 Recently, our group and others have expanded the scope of PA imaging through the development of acoustogenic ABS probes. 9,10 Select examples include imaging agents for the detection of metal ion dysregulation, [11][12][13][14] hypoxia, [15][16][17][18] proteases, 19,20 and signaling molecules (e.g., nitric oxide 21,22 and hydrogen sulfide 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can afford high resolution images in deep tissue based on optical absorption. PAT has shown its ability in breast cancer [21][22][23], thyroid cancer [24,25], vascular examination [4,[26][27][28][29], inflammatory arthritis and osteoarthritis [30][31][32], oral cancer [33][34][35], bone pathology [36] and dermatology [37][38][39] in human studies. PAT of vasculature can be achieved because hemoglobin is concentrated in blood vessels with strong optical absorption.…”
Section: Introductionmentioning
confidence: 99%